2017
DOI: 10.1002/ijc.30526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on cancer mortality and progression: A systematic review and meta‐analysis of 95 cohorts including 1,111,407 individuals

Abstract: Statins have been implicated in the regulation of cell proliferation, apoptosis and tumor progression in cancer patients and statin use at the time of cancer diagnosis has been reported to be associated with reduced cancer risk and improved survival, irrespective of concomitant anti-cancer therapy. A systematic literature search of relevant databases through May 2015 was conducted to identify studies assessing the prognostic impact of statin use on prognostic outcomes in cancer patients. Literature search iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 127 publications
6
92
0
2
Order By: Relevance
“…[14][15][16][17][18][19][20][21] However, to date, although head and neck cancer cells are considered to be sensitive to statins, most previous studies only attempted to find the relationship between statins and many types of cancers, but not head and neck cancers. [22][23][24][25][26][27] Only 1 Western study mentioned that statin usage may decrease the risk of death from pharynx cancer. 28 No prior study explored the connection between statins and the incidence of head and neck cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] However, to date, although head and neck cancer cells are considered to be sensitive to statins, most previous studies only attempted to find the relationship between statins and many types of cancers, but not head and neck cancers. [22][23][24][25][26][27] Only 1 Western study mentioned that statin usage may decrease the risk of death from pharynx cancer. 28 No prior study explored the connection between statins and the incidence of head and neck cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Statin therapy is frequently used in diabetic patients for the prevention of cardiovascular complications, but a recent large meta‐analysis showed that statin therapy was associated with reduced cancer‐specific mortality as well (HR 0.60, 0.47–0.77) . Conversely, recently some observational studies, and clinical trials have not detected any effect on survival.…”
mentioning
confidence: 99%
“…Preclinical studies 7 -10 have demonstrated antiproliferative, proapoptotic and antimetastatic effects of statins in OAC. A recent systematic review 14 of observational studies, which included 95 cohorts with over a million patients with cancer at numerous primary sites, demonstrated that statin use after diagnosis was associated with significant reductions in all-cause mortality (pooled hazard ratio (HR) 0⋅65, 95 per cent c.i. A recent systematic review 14 of observational studies, which included 95 cohorts with over a million patients with cancer at numerous primary sites, demonstrated that statin use after diagnosis was associated with significant reductions in all-cause mortality (pooled hazard ratio (HR) 0⋅65, 95 per cent c.i.…”
Section: Introductionmentioning
confidence: 99%